Cyclin-dependent kinase-mediated phosphorylation of breast cancer metastasis suppressor 1 (BRMS1) affects cell migration. Issue 1 (2nd January 2016) - Roesley, Siti Nur Ain; Suryadinata, Randy; Morrish, Emma; Tan, Anthonius Ricardo; Issa, Samah M. A.; Oakhill, Jonathan S.; Bernard, Ora; Welch, Danny R.; Šarčević, Boris
ABSTRACT: Expression of Breast Cancer Metastasis Suppressor 1 (BRMS1) reduces the incidence of metastasis in many human cancers, without affecting tumorigenesis. BRMS1 carries out this function through several mechanisms, including regulation of gene expression by binding to the mSin3/histone deacetylase (HDAC) transcriptional repressor complex. In the present study, we show that BRMS1 is a novel substrate of Cyclin-Dependent Kinase 2 (CDK2) that is phosphorylated on serine 237 (S237). Although CDKs are known to regulate cell cycle progression, the mutation of BRMS1 on serine 237 did not affect cell cycle progression and proliferation of MDA-MB-231 breast cancer cells; however, their migration was affected. Phosphorylation of BRMS1 does not affect its association with the mSin3/HDAC transcriptional repressor complex or its transcriptional repressor activity. The serine 237 phosphorylation site is immediately proximal to a C-terminal nuclear localization sequence that plays an important role in BRMS1-mediated metastasis suppression but phosphorylation does not control BRMS1 subcellular localization. Our studies demonstrate that CDK-mediated phosphorylation of BRMS1 regulates the migration of tumor cells.